Quality of Life in Children with Nephrotic Syndrome at Dr. Moewardi Hospital - Kartawijaya, Andrew Andy Putra; Nugroho, Hari Wahyu; Nur, Fadhilah Tia (Journal of Maternal and Child Health, 2021)
Background: Children with chronic disease often have poor quality of life. Nephrotic syndrome was one of the most common kidney diseases in children with a high number of relapses. Therefore, treatment for nephrotic syndrome might take a long time. Complications from the disease and medications might affect the quality of life of the patient. Subjects and methods: This was a cross sectional, descriptive analytic study. Children aged 5-18 years old who visited the nephrologic outpatient department of Dr Moewardi general hospital from july to September 2020 and fullfilled the inclusion criteria were included in the study. Quality of life was assessed using PedsQLTM 4.0 generic module.The analysis of this research was done by using chi-square and logistic regression. Results: A total of 27 children aged from 5-18 years old participated in this study. Decrease quality of life was reported in 22% based on report from parents. From parent’s report, gender (OR= 0.06; CI95%= 0.01 to 0.66; p= 0.008) was associated with decrease of quality of life in children with nephrotic syndrome. Most of the children had decreased quality of life in the psychososial domain according to parent’s report (OR= 4.70; 95% CI= 1.12 to 19.70; p= 0.026). Conclusion: 22% children with nephritic syndrome have decreased quality of life. Gender was the risk factors that might contribute to the decreased quality of life of children with nephrotic syndrome.